Through-Space Effects of Substituents Dominate Molecular Electrostatic Potentials of Substituted Arenes - Wheeler, Steven E. (2009)
Model systems have been studied using density functional theory to assess the contributions of π-resonance and through-space effects on electrostatic potentials of substituted arenes. The results contradict the widespread assumption that changes in molecular ESPs reflect only local changes in the electron density. Substituent effects on the ESP above the molecular plane are commonly attributed to changes in the aryl π-system. We show that ESP changes for a collection of substituted benzenes and more complex aromatic systems can be accounted for mostly by through-space effects, with no change in the aryl π-electron density. Only when π-resonance effects are substantial do they influence changes in the ESP above the aromatic ring to any extent. Examples of substituted arenes studied here are taken from the fields of drug design, host-guest chemistry, and crystal engineering. These findings emphasize the potential pitfalls of assuming ESP changes reflect changes in the local electron density. Since ESP changes are frequently used to rationalize and predict intermolecular interactions, these findings have profound implications for our understanding of substituent effects in countless areas of chemistry and molecular biology. Specifically, in many non-covalent interactions there are significant, often neglected, through-space interactions with the substituents. Finally, the present results explain the perhaps unexpectedly good performance of many molecular mechanics force-fields applied to supramolecular assembly phenomena and π-π interactions in biological systems despite the neglect of the polarization of the aryl π-system by substituents.